DEVELOPING INDEPENDENT MEDIA EDUCATION THROUGH ONLINE PLATFORMS (YOUTUBE, COURSERA) - Tog’ayeva Muattar Bahodir qizi (TADQIQOTLAR, 2026)
Annotation: The rapid development of digital technologies has transformed the educational landscape, enabling learners to access knowledge independently through online platforms. This article explores the role of platforms such as YouTube and Coursera in fostering independent media education. The study examines how these platforms contribute to the development of media literacy, critical thinking, and self- directed learning skills. Using a mixed-method approach, including content analysis and learner feedback, the research highlights the effectiveness of online platforms in enhancing media competence. The findings indicate that these platforms provide flexible, accessible, and diverse learning opportunities, although challenges such as information overload and lack of guidance remain. The article concludes with recommendations for optimizing the use of online platforms in media education.